Upper-Critical-Solution-Temperature Polymer Modified Gold Nanorods for Laser Controlled Drug Release and Enhanced Anti-Tumour Therapy - Lin, Que; Jia, Mao; Fu, Yi; Li, Bei; Dong, Zhigang; Niu, Xiaoya; You, Zhen (Frontiers in Pharmacology, 2021)
Photothermal therapy (PTT) has become effective method for the treatment of malignant cancer. The development of PTT system with high anti-tumour effect is still the feasible research direction. Here, a new type of gold nanorods (AuNRs)-doxorubicin (DOX)/mPEG10K-peptide/P(AAm-co-AN) (APP-DOX) nano drug delivery system was proposed. Among them, AuNRs was used as high-efficiency photothermal agent. APP-DOX had a suitable size and can be targeted to accumulate in tumour tissues through circulation in the body. The abundant matrix metalloproteinase 2 (MMP-2) in the tumour environment intercepted and cut off the short peptide chain structure grafted on APP-DOX. At the same time, the removal of the PEG segment leaded to an increase in the hydrophobic properties of the system. Nanoparticles aggregated into large particles, causing them to stay and aggregate further at the tumour site. When irradiated by 808 nm near-infrared laser, APP-DOX achieved a gradual heating process. High temperature can effectively ablate tumours and enable UCST polymer to achieve phase transition, resulting in more anti-cancer drugs loaded in the polymer layer DOX was released, effectively killing cancer cells. Animal experiments had verified the possibility of the nano drug-carrying system and good tumour treatment effect. What's more worth mentioning is that compared with free DOX, the nano drug delivery system had lower biological toxicity and not cause obvious harmful effects on normal organs and tissues.